RFID-Based IoT Scanning System for Tracking Parking Slot Application - Heru Wijanarko; Siti Nurhafizha; Asrizal Deri Futra; Kamarudin Kamarudin; Dessy Oktani; Muhammad Syafei Gozali; Junaedi Adi Prasetyo; Rahmi Mahdaliza (Journal of Applied Electrical Engineering, 2023)
The increasing demand for parking spaces in various facilities, such as shopping centers, ports, and airports, poses a significant challenge for parking managers. Drivers waste time and fuel searching for available parking slots, resulting in increased air pollution and negative environmental and health impacts. Therefore, a new solution is needed to address these issues and improve parking management efficiency. A parking management system that utilizes RFID technology and allows for the RFID Tag on each car to display user data, user ID, and parking space reservations is needed to improve the efficiency and convenience of parking at various facilities. The proposed system design incorporates various components, including a Camera Sensor, Raspberry PI, ESP8266, UHF RFID reader, and RFID Tag. The RFID technology captures radio waves emitted by the RFID Tag, enabling individual identification through unique codes. Testing revealed high accuracy at close range but decreased effectiveness at longer distances. Internet speed and network latency affected system performance, with faster speeds enabling faster data transmission. The system, developed using Thunkable and Firebase, provides real-time parking space availability information and streamlines vehicle entry and exit processes through RFID technology. This system has the potential to greatly improve the parking experience at busy public facilities by facilitating efficient parking spot finding and enhancing overall convenience for drivers.